Analysis of the Mental Health Bill, 2014: Submission to the Health Committee of the Parliament of Uganda on February 8, 2018 - Initiative for Social and Economic Rights (ISER) (Initiative for Social and Economic Rights (ISER), 2018)
The current legislation governing mental health in Uganda is the Mental Treatment Act, Cap 279 which was enacted in 1964. It has long been overtaken by key developments and interventions including, and most importantly, the adoption of the United Nations Convention on the Rights of Persons with Disabilities (CRPD)1 and its ratification by Uganda. From the use of derogatory terms such as ‘idiots’ and ‘persons suffering from mental derangement’ to subjecting PWDs to forced medical interventions without consent, and detention for indeterminable periods of time, the Mental Treatment Act violates the human rights of persons with psychosocial and intellectual disabilities to dignity, physical and mental integrity, independence, liberty, and freedom from cruel, inhuman and degrading treatment.